REVIEW OFCHROMITE DEPOSITS OF INDONESIA - Ernowo, Ernowo; Oktaviani, Penny (Buletin Sumber Daya Geologi, 2010)
Chromites (Fe,Mg)Cr O is an oxide mineral in spinel group. It is one of metallic mineral which classified in to alloy and ferro alloy metallic mineral group along with iron, nickel, titanium, manganese, cobalt, and bauxite. Chromites is the only ore mineral of metallic chromium and chromium compounds and chemicals. Because of this fact, chromites and chrome ore are used synonymously in trade literature. It is used for refractory material, because it has high heat stability. In Indonesia, chromites deposits are widely distributed in the eastern part of Indonesia, which rich in metal bearing ultramafic to mafic intrusive especially in South Kalimantan, Sulawesi, Maluku, Halmahera, Gebe, Gag, Waigeo, and Papua. These deposits are resulted from weathering of ophiolite rocks as part of the Pacific plate.